2017
DOI: 10.1186/s41936-017-0001-7
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of silver nanoparticles on fertilization success and early development of the marine polychaete Hydroides elegans (Haswell, 1883)

Abstract: Background: The silver nanoparticles (AgNPs) are used in the production of numerous commercial and medical products and are found to have adverse effects on animals. The sessile marine polychaete worm, Hydroides elegans, was examined for the influence of AgNPs on external fertilization and early developmental stages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Similar studies using sea urchin sperm of Paracentrotus lividus have also revealed genotoxic properties of ZnO and CuO NPs [ 27 , 43 ]. In addition, the genome sensitivity of male gametes to various nanoparticles has been shown in other marine invertebrates, including the bivalve Tegillarca granosa [ 44 ], the polychaete Hydroides elegans [ 45 ] and the ascidia Ciona intestinalis [ 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…Similar studies using sea urchin sperm of Paracentrotus lividus have also revealed genotoxic properties of ZnO and CuO NPs [ 27 , 43 ]. In addition, the genome sensitivity of male gametes to various nanoparticles has been shown in other marine invertebrates, including the bivalve Tegillarca granosa [ 44 ], the polychaete Hydroides elegans [ 45 ] and the ascidia Ciona intestinalis [ 46 ].…”
Section: Resultsmentioning
confidence: 99%